Successful use of vancomycin hydrochloride in the treatment of lactulose resistant chronic hepatic encephalopathy. Issue 6 (June 1990) - Tarao, K; Ikeda, T; Hayashi, K; Sakurai, A; Okada, T; Ito, T; Karube, H; Nomoto, T; Mizuno, T; Shindo, K
Abstract : Vancomycin hydrochloride (2 g daily) was administered to 12 patients with cirrhosis and lactulose resistant portal systemic encephalopathy in a double blind crossover trial. All 12 patients showed a remarkable clinical improvement after vancomycin treatment. The mean (SE) electroencephalographic (EEG) frequency changed from 6.3 (0.2) to 8.5 (0.2) cps (p less than 0.001) and the mean arterial ammonia concentration from 152 (4) micrograms/ml to 97 (8) micrograms/ml (p less than 0.001). Their clinical condition deteriorated when treatment was switched to lactulose, returning to the previous slower EEG frequency and high arterial ammonia concentrations. Vancomycin seems to be effective in chronic portal systemic encephalopathy in patients who are not helped by lactulose alone.